Desenvolvimento de um sistema de emulação de Single Event Upsets em dispositivos COTS baseado na metodologia Code Emulating Upsets - Fernando Esquirio Torres (2013)
This work presents a method and a tool that enable the emulation of the behavior of Single Event Upset faults in applications running on microcontrollers COTS installed in scientific satellites, which are designed to operate in low Earths orbit. The method presented in this work aims to validate computational systems developed with techniques for fault tolerance, which are built from these devices. The tool developed in this work, called PORTHES, is based on a fault emulating methodology known as Code Emulating Upsets, that allows to emulate the behavior of faults through a piece of code inserted as an Interrupt Service Routine into the firmware of the application running in the microcontroller, which allows the simulation of upsets in the device-application under test, reproducing the effects of ionizing radiation of low Earth orbit in space environment. The PORTHES system was developed to be a portable tool, and was constructed with low cost equipment. Moreover, the system doesnt need to build a hardware-specific board to validate microcontrollers to SEUs. The system is controlled by a graphical user interface that is running on a computer. The graphical user interface allows to configure the variables and to control the actions used in the experimental process, the fault generation, the emulation of faults behavior and the data analysis. The PORTHES is used to investigate the operation of applications running on COTS microcontrollers in the presence of faults and also it is useful to be employed to validate systems developed with these devices and fault tolerance techniques, without need to submit the system to a process of ionizing radiation exposure. The experimental sessions indicated that the system PORTHES can be used as a tool for emulation of Single Event Upsets faults in applications running on microcontrollers COTS and the system may be able to execute tests as if the device-application was exposed to ionizing radiation of low Earth orbit in space environment.